Effect of odd-viscosity on the dynamics and stability of a thin liquid film flowing down on a vertical moving plate. (April 2022) - Chattopadhyay, Souradip; Subedar, Gowri Y.; Gaonkar, Amar K.; Barua, Amlan K.; Mukhopadhyay, Anandamoy
Abstract: In this study, we focus on the problem of hydrodynamic instability of a thin, viscous, Newtonian liquid film with broken time-reversal-symmetry flowing down along the surface of a vertical moving plate. The presence of odd viscosity gives rise to new terms in the pressure gradient of the flow. Utilizing the classical long-wave perturbation method, we obtain the analytical solutions as well as derive the nonlinear evolution equation of Benney-type in terms of film thickness h ( x, t ) which is significantly modified due to the presence of odd viscosity in the liquid. We solve the linear model by using the normal mode approach and for three different conditions, namely, the quiescent, up-moving and down-moving plate velocity. The linear study shows that the effect of the down-moving motion of the vertical plate is to enhance the stability of the film flow whereas the up-moving motion of the vertical plate tends to reduce it. Further, the study shows that odd viscosity always has a stabilizing effect on the flow field. In addition, the Orr–Sommerfeld equation is also derived and solved analytically to obtain the critical Reynolds number. Finally, we show the numerical solution of the evolution equation in a periodic domain which clearly demonstrates the role of odd-viscosity on the dynamics of the plate motions of thin film flows coating in isothermal environments. Our study clearly shows how odd viscosity influences the stability of the flow. Highlights: Odd-viscosity plays a vital stabilizing role on the flow. The moving style of the plate significantly affects the stability of the flow. Nonlinear stability analysis by means of numerical simulations.